2013
DOI: 10.1590/s1516-05722013000500010
|View full text |Cite
|
Sign up to set email alerts
|

Prospecção fitoquímica preliminar de plantas nativas do cerrado de uso popular medicinal pela comunidade rural do assentamento vale verde - Tocantins

Abstract: Este estudo objetivou caracterizar qualitativamente grupos de metabólitos secundários e alguns constituintes de 9 espécies de plantas medicinais nativas do cerrado utilizadas pela comunidade rural do Assentamento Vale Verde, identificando potencialidades biológicas e farmacológicas. As informações referentes às plantas de uso medicinal foram obtidas por meio de estudos etnobotânicos e etnofarmacológicos, realizados no período de 2010 a 2012. O material botânico coletado foi identificado e depositado no Herbári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
47

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 58 publications
1
27
0
47
Order By: Relevance
“…In present study, presence of saponins was not observed and this fact was confirmed by the various researcher when they were working on the other species such as Spondias tuberosa Arr Cam (umbu), A. occidentale (Cashew) and M. indica (mango) of the same family (Silva et al, 2008;Bessa et al, 2013;Silva & Almeida, 2013), although work done with Spondias mombin (Asuquo et al, 2013), Myracrodruon urundeuva and Spondias pinnata, revealed the presence of saponins (Dantas et al, 2008).…”
Section: Resultssupporting
confidence: 79%
“…In present study, presence of saponins was not observed and this fact was confirmed by the various researcher when they were working on the other species such as Spondias tuberosa Arr Cam (umbu), A. occidentale (Cashew) and M. indica (mango) of the same family (Silva et al, 2008;Bessa et al, 2013;Silva & Almeida, 2013), although work done with Spondias mombin (Asuquo et al, 2013), Myracrodruon urundeuva and Spondias pinnata, revealed the presence of saponins (Dantas et al, 2008).…”
Section: Resultssupporting
confidence: 79%
“…However, the same authors addressed the importance of performing these tests as a mechanism to direct the fractionation of crude extracts and to identify active components to allow biological assays to be performed. This was corroborated by Bessa et al (2013) who mentioned that this easy to perform, fast, and inexpensive technique is important in preliminary studies on plants considering that the phytochemical profile is still not widely studied.…”
Section: Resultsmentioning
confidence: 74%
“…E-mail: raica@assis.unesp.br. All phytochemical screening was performed according to the recommendations from previous study (Collins and Braga, 1988;Simões et al, 2010;Bessa et al, 2013 …”
Section: Animalsmentioning
confidence: 99%